Lychee tree parameters for water balance modeling - K. Spohrer (2018)
Lychee (Litchi chinensis Sonn.) is widely grown under irrigation in the tropical northern Thailand highlands. Water efficient irrigation requires sound irrigation scheduling for which the requisite soil moisture information can be obtained from water balance modeling. A prerequisite for water balance predictions are plant parameters which describe interception, root distribution evaporation and transpiration. These parameters depend on climate, soil, as well as plant physiology, variety and age. This study investigated the plant parameters for 7-year-old lychee trees in tropical granite landscapes, as they are as yet unavailable. Interception could be satisfactorily predicted with the modified Gash model. The Gash parameters (canopy capacity per canopy cover area (Sc), canopy cover factor (c)) were determined to be 21.8 mm and 0.22, respectively. The spatial distribution of lychee tree roots depended on slope inclination. On the level plateau position, root length density (RLD) distribution was trunk-symmetrical and could be predicted with an empirical function. On the slope, the asymmetrical and irregular root development was not predictable. The suitability of the dual crop coefficient approach predicting daily potential evaporation (Epot) and daily potential transpiration (Tpot) rates for water balance modeling was limited due to the weak correlations of Epotand Tpotwith the potential reference evapotranspiration (ETo). As a result, no universal values for the potential evaporation coefficient (Ke,max) and the potential transpiration coefficient (Kcb) could be determined. Hence, Epotand Tpotmeasurements are mandatory if accurate Epotand Tpotdata are necessary. In the case of missing measurements, Ke,maxvalues of 0.6 and 1.6 are recommended for rough Epotestimates underneath and in-between the lychee tree canopies. For Tpotpredictions in irrigation scheduling, a relatively high Kcbof 0.8 is recommended in order to ensure a water stress free fruit development within the irrigation season. © Springer 2006.